2016
DOI: 10.1007/s13244-016-0520-7
|View full text |Cite
|
Sign up to set email alerts
|

Causes of hepatic capsular retraction: a pictorial essay

Abstract: Hepatic capsular retraction refers to the loss of the normal convex hepatic contour, with the formation of an area of flattening or concavity. This can result from myriad causes, including intrinsic hepatic conditions such as cirrhosis, biliary obstruction, benign tumours, malignancy and infections, as well as extrahepatic causes such as trauma. This article aims to provide familiarity with this wide spectrum of conditions, including mimics of hepatic capsular retraction, by highlighting the anatomic, patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…After 14 and 30 days of treatment, the morphology of the liver was affected, several pits were seen on its surface and they were more prominent in the 30 days group, it appeared that inflammation is the main cause, change in the liver's color from normal brown-red to yellowish color and white spots were also seen, the liver was hard and increased in size, this may be a sign of liver fibrosis (24) and the toxicity of the drug. In the present study, the histopathological findings showed that there are different and obvious effects in liver tissue of the treated groups for 14 and 30 days, the results indicated that administration of CBZ distorts Glisson`s capsule, the disappearance of the natural convex of the capsule with the appearance of a sub capsular space which was caused by hepatic contour retraction, this can result from several causes including cirrhosis, infection, benign and malignant tumors (25). Cytologic alterations were also present in the treated groups for 14 and 30 days, these alterations manifested in the appearance of dark and light areas, which could be related to the microsomal enzyme induction or the peroxisomes proliferation (26), and smooth endoplasmic reticulum proliferation which is also seen in cases related to Phenobarbital treatment for epilepsy (27).Hydropic degeneration and ballooning degeneration are known to occur after CBZ treatment (28) hepatocytes appeared swollen and round in shape due to fluid accumulation with a central dark nucleus and pale cytoplasm, this degeneration and the cytoplasmic changes are the results of cloudy swelling that is known to be a form of cell death, it happens after an increase in Na + and K+ ions inside the cells (29).Organelles swelling such as SER is noticed in the hepatocytes, it is generally accepted that the chronic use of antiepileptic drugs can cause cell death of all kinds such as neurons when drugs like PHT and VPA were used (30).…”
Section: -Disscusionmentioning
confidence: 45%
“…After 14 and 30 days of treatment, the morphology of the liver was affected, several pits were seen on its surface and they were more prominent in the 30 days group, it appeared that inflammation is the main cause, change in the liver's color from normal brown-red to yellowish color and white spots were also seen, the liver was hard and increased in size, this may be a sign of liver fibrosis (24) and the toxicity of the drug. In the present study, the histopathological findings showed that there are different and obvious effects in liver tissue of the treated groups for 14 and 30 days, the results indicated that administration of CBZ distorts Glisson`s capsule, the disappearance of the natural convex of the capsule with the appearance of a sub capsular space which was caused by hepatic contour retraction, this can result from several causes including cirrhosis, infection, benign and malignant tumors (25). Cytologic alterations were also present in the treated groups for 14 and 30 days, these alterations manifested in the appearance of dark and light areas, which could be related to the microsomal enzyme induction or the peroxisomes proliferation (26), and smooth endoplasmic reticulum proliferation which is also seen in cases related to Phenobarbital treatment for epilepsy (27).Hydropic degeneration and ballooning degeneration are known to occur after CBZ treatment (28) hepatocytes appeared swollen and round in shape due to fluid accumulation with a central dark nucleus and pale cytoplasm, this degeneration and the cytoplasmic changes are the results of cloudy swelling that is known to be a form of cell death, it happens after an increase in Na + and K+ ions inside the cells (29).Organelles swelling such as SER is noticed in the hepatocytes, it is generally accepted that the chronic use of antiepileptic drugs can cause cell death of all kinds such as neurons when drugs like PHT and VPA were used (30).…”
Section: -Disscusionmentioning
confidence: 45%
“…The blood supply to the right lobe has more influence usually because the right portal vein enters the right lobe directly (23). These events lead to morphological changes, including enlargement of the caudate and left liver lobes, and atrophy of the right lobe (26,27). Although these shape features have been used for the diagnosis of many tumors in clinical practice (28), using appearance alone to diagnose cirrhosis is subjective.…”
Section: Discussionmentioning
confidence: 99%
“…The fat attenuation of PGCs allows them to be easily distinguished from serosal metastases [8]. Besides serosal metastasis are FDG avid [9]. Solitary necrotic nodules are described in literature as intraparenchymal, in a peripheral location, with a propensity to involve the right hepatic lobe.…”
Section: Discussionmentioning
confidence: 99%